KEKOHERENAN ANTARA MATERI ARITMETIKA DAN ALJABAR DI SEKOLAH MENENGAH PERTAMA - Putri, Zakiah Norma; Sugiatno, Sugiatno; Nursangaji, Asep (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe research was conducted because of there was tendency of textbooks that became the reference when teaching had aspects of mathematical comunication that were not optimal where as teachers and students used the textbooks.The purpose of this study is to explain the coherence between the presentation of aspects of communication, mathematical conceptual understanding in material operation numbers (arithmetic) and expressions in the junior high school textbooks. The coherence between the presentation of aspects of communication and mathematical conceptual understanding in mathematics textbook to present the correct concepts and the correct communication that is arranged consistently and thoroughly. This research method is a descriptive method, the main form of this study is interrelationshipstudies, there are three books that will be examined with the instrument used in this study is the assessment rubric. The assessment rubric contains aspects of communication coherence and conceptual understanding in the textbook. The coherence aspect of mathematical communication in thehighest mathematical textbooks is 75% whereas the Coherence between the dimensions of mathematical communication and conceptual understanding in mathematics textbooks has a presentation of research results <70%, it’s cause of unavailabletextbooks with clear connection and continuous coherence between the correct communication and the correct concept. Keywords:Coherence, Mathematic Communication, Conceptual understanding Mathematic